The violation of the principle of minimum intervention of criminal law in relation to the minimum possession of two or more types of drugs - Torres Campos, Jhordy Michel (2023)
This article addresses an issue of great relevance regarding the regulation contained in the second paragraph of Article 299 of the Penal Code. This legal provision raises concerns due to its exclusion from the exemption of criminal liability in situations where possession involves two or more types of drugs. This regulation is problematic in terms of compatibility with the principle of minimal intervention of Criminal Law. In this context, the need to modify the mentioned article is raised, in order to encompass within its notion of non-punishable possession the possession of drugs intended for one's own immediate consumption, regardless of whether it involves one or several types of substances, as long as the stipulated minimum quantities are respected. It is important to emphasize that this modification would not apply in cases where possession serves purposes other than personal consumption. Consequently, this proposal seeks to offer a more coherent and in line with the principle of minimal intervention, while addressing a relevant issue in the penal domain.